Current plate boundary deformation of the Afar rift from a 3‐D velocity field inversion of InSAR and GPS. Issue 11 (28th November 2014) - Pagli, Carolina; Wang, Hua; Wright, Tim J.; Calais, Eric; Lewi, Elias
Abstract Extension, faulting, and magmatism are the main controls on the magnitude and localization of strain at mid‐ocean ridges. However, the temporal and spatial patterns of such processes are not clear since the strain distribution has not been resolved in the past at sufficient spatial resolution and over extended areas. Interferometric synthetic aperture radar (InSAR) and GPS data with unprecedented resolution are now available to us from the Afar rift of Ethiopia. Here we use a velocity field method to combine InSAR and GPS to form the first high‐resolution continuous three‐dimensional velocity field of Afar. We study an area that is 500 km wide and 700 km long, covering three branches of the Afar continental rift and their triple junctions. Our velocity field shows that plate spreading is currently achieved in Afar in contrasting modes. A transient postdiking deformation is focused at the Dabbahu rift segment, while in central Afar, spreading is distributed over several overlapping segments and southern Afar exhibits an interdiking deformation pattern focused at the Asal–Ghoubbet segment. We find that current spreading rates at Dabbahu, following the 2005–2010 intrusions, are up to 110 mm/yr, 6 times larger than the long‐term plate divergence. A segment‐centered uplift of up to 80 mm/yr also occurs, indicating that magma flow is still a primary mechanism of deformation during postdiking. On the other hand, no vertical displacements are currently observed in central and southern Afar, suggesting lack of significant magmatic activity at shallow levels.